Numerical Simulation and Optimization of Outdoor Wind Environment in High-Rise Buildings Zone of Xuzhou City - Huanhuan Fang; Xiang Ji; Jiuxin Wang; Jijun Lu; Mengcheng Yang; Jiajun Li; Zhongcheng Duan (Buildings, 2025)
High-rise developments frequently exert adverse impacts on the outdoor wind environment, leading to a deterioration in the overall quality of urban surroundings and a reduction in the comfort levels of residents. This study systematically investigates typical high-rise settlements in Xuzhou City and proposes optimization strategies to address wind environment issues through an in-depth analysis of building planning parameters. Utilizing Computational Fluid Dynamics (CFD) simulations, the research identifies key wind-related challenges associated with high-rise buildings in representative settlements. The study comprehensively examines the effects of building height, width, orientation, spacing, and layout on the outdoor wind field, progressing from individual building units to clusters. Based on these findings, optimization strategies are formulated and validated through CFD simulations conducted on a representative high-rise settlement in Xuzhou. The results reveal that typical high-rise buildings in Xuzhou exhibit a height of 54 m, a width of 48 m, and an orientation ranging from 15° to 30° southeast. The front-to-rear building spacing is approximately 1.44 times the building height, with an additional 15 m spacing from mountain walls. Optimal wind conditions are achieved with a center-vacant building layout. The optimization of building form, spacing, and orientation substantially improves the outdoor wind environment by alleviating stagnant wind zones and reducing wind pressure differentials between the building fronts and rears, thereby enhancing the comfort of residents. This study provides a valuable reference for the planning and design of high-rise settlements, contributing to an improvement in urban environmental quality and the enhancement of livability.